(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Peripheral Obstructive Arterial Disease (PAD) is a condition in which there is a narrowing or blockage of the arteries that supply the lower limbs. The main objective of this systematic review was to identify studies that addressed the pathophysiology, epidemiology and signs and symptoms of PAD, with special emphasis on surgical intervention strategies. Methods:The search was conducted in renowned databases such as PubMed, Scopus, SciELO, Cochrane Library, LILACS, UpToDate and Embase, using controlled descriptors from DeCS. In order to effectively search for studies, descriptors such as "Peripheral Arterial Disease", "Vascular Surgical Procedures", "Myocardial Revascularization", "Angioplasty", "Vascular Grafting", "Thromboendarterectomy" and "Vascular Surgery" were used. These descriptors were combined with Boolean operators "OR" and "AND" to improve the precision of the search. The methodological approach adopted allowed for a thorough and comprehensive search, ensuring the inclusion of relevant studies. Results: The final sample consisted of 28 articles published in indexed scientific journals, addressing different aspects of POAD, such as symptomatology, epidemiology and surgical approach. The articles were available in full for analysis and were written in Portuguese. Analysis of the studies provided a better understanding of the pathophysiology of POAD, identified the main symptoms and examined the different surgical approaches used in treatment.Conclusion: The comprehensive systematic review of the literature on POAD provided valuable information on the disease and its surgical treatment modalities. The results obtained are essential for guiding clinical practice and assisting in decision-making regarding the management of POAD. The methodological approach adopted ensured the inclusion of relevant studies and provided a solid basis for understanding PAOD and providing appropriate care to patients.